New regionalism in Bali architecture by Popo Danes - Akmal, Imelda; Sandjaya, Sonny (Jakarta, Indonesia : Imaji, 2011)
Regionalism is an apt to describe Popo Danes' architectural designing pattern. Popo Danes' architectural works demonstrate the flexibility of Balinese in accepting modernization while preserving their distinctive Bali identity. This book does not only exhibit beautiful architectural works, but also describes how Popo Danes' works have contributed and shaped the characteristics of Bali today. Popo Danes is one of Bali's established and famous architects. He is also one of the most productive since the beginning of his career until now. This monograph of Popo Danes describes more than 30 of his architectural projects spanning from houses, villas, hotels, restaurants, musems and old building conservations. Some of these projects have won several awards and are considered as Indonesia's architectural assets.
1. Boutique hotel and resort -- 2. Private villa and residence -- 3. Conservation -- 4. Museum and office -- Recent Projects -- Popo Danes biography -- Time line and photo location.
Keywords: ARCHITECTURE -- INDONESIA -- BALI ISLAND